Anticholinergic burden is associated with recurrent and injurious falls in older individuals. (February 2016) - Zia, Anam; Kamaruzzaman, S.; Myint, Phyo Kyaw; Tan, M.P.
Highlights: Individuals with recurrent or injurious falls are more likely to consume medications with anticholinergic properties. The anticholinergic cognitive burden (ACB) score alongside TUG and FR may be useful tools for assessment of risk factors for falls As grip strength was unaffected, impaired lower limb function may be due to the central effects of ACB. Abstract: Objective: While the anticholinergic activity of medications has been linked to cognitive decline, few studies have linked anticholinergic burden with falls in older people. We evaluated the relationship between anticholinergic burden and recurrent and injurious falls among community-dwelling older adults. Study design: This case-control study was performed on 428 participants aged ≥65 years, 263 cases with two or more falls or one injurious fall in the preceding 12 months, and 165 controls with no falls in the preceding 12 months. Anticholinergic burden was determined using the anticholinergic cognitive burden (ACB) scale. Upper and lower limb functional abilities were assessed with timed up and go (TUG), functional reach (FR) and grip strength (GS). Logistic regression analysis was employed to calculate the mediation effect of TUG, FR and GS on ACB associated falls. Results: Univariate analysis revealed a significant association between an ACB score of ≥1 with falls (OR, 1.8; 95% CI; 1.1–3.0; p = 0.01) and significantly poorer TUG and FR. The association between ACB≥1 and falls was no longer significant after adjustment for either TUG (OR for ACB associated falls, 1.4; 95% CI, 0.88–2.4; p = 0.14) or FR (OR for ACB associated falls, 1.4; 95% CI, 0.89–2.4, p = 0.12) but remained significant with GS. Conclusion: The association between recurrent and injurious falls and the use of any medications listed in the ACB scale was mediated through gait and balance impairment but not by muscular weakness, providing a novel insight into the potential mechanistic link between ACB and falls. Future studies should determine whether TUG and FR measurements could help inform risk to benefit decisions where ACB medications are being considered.